(untitled) - Clark, Gordon L. (New York, 2004)
The key arguments and debates about globalization have raised searching questions about the significance of national and regional borders for the competitive strategies of individuals, firms and industries. Global Competitiveness and Innovation seeks to address these issues by exploring four key topics: The status of economic agents in the emerging global economy; the limits of path dependence and the scope of agent action; the relationship between agents' decision-making and their environments; and agents' learning capacities in a world of information and knowledge creation.
Keywords: Competition, international,Competition,International economic relations,Globalization